The Fed-Strategy: Successful but out-of-date? - Daniel Hartmann (Universität Hohenheim, 2002)
Opinion about the American monetary policy of the past 10-15 years is divided. On the one hand several economists are convinced that the wise policy of the Federal Reserve (Fed) has mainly contributed to the exceptional performance of the US economy in the 1990s. This performance has been especially great in the second half of the 1990s with real growth rates of more than 3.5 % and low inflation rates of about 2 %. This is why some economists call the 1990s the "Fabulous Decade". On the other hand the strategy of the Fed is strongly criticized. While other central banks like the Bank of England or the European Central Bank (ECB) have made intensive efforts to present the general public with a clear and comprehensible strategy the Fed is - according to these critics - lacking such a clear framework. Instead of a well-articulated strategy the Fed has its "Magician" Greenspan. Some economists have meanwhile described the Fed as one of the most opaque and unclear central banks (among the most prominent ones). This paper will attempt to examine if these reproaches against the Fed-Strategy are justified and if the Fed should revise its policy concept. The paper firstly describes the current framework of the Fed, especially its targets and its operational procedure and shows possible deficits. The result of this theoretical analysis suggests in fact that the Fed's behavior is neither rule-orientated nor transparent. But as can be shown in the second part of the paper this academic and critical view of the Fed policy contradicts the market's opinion about the Fed policy. From the markets' perspective the Fed-Strategy seems to be highly transparent and credible. The paper proceeds as follows: The second section touches briefly on the issue as to why it might be important for a central bank to present a clear monetary policy strategy. Section 3 takes a close look at the targets of the Fed. Section 4 describes the current procedure of the Fed in monetary policy and tries to assign the Fed-Strategy to a common framework such as Inflation Targeting or the Taylor-Rule. Section 5 looks at the Fed-Strategy from the markets' perspective, especially the markets' judgment about the credibility and transparency of the Fed as being of central interest.
urn:nbn:de:bsz:100-opus-4536
Keywords: 330